The Influence of Leadership, Culture and Organizational Commitment on Employee Performance at the Personnel and Human Resources Development Agency of Lamandau Regency, Central Kalimantan Province - Lesmana, Hendra; Ruspitasari, Widi Dewi; Murtianingsih, Murtianingsih (CV. Rayyan Dwi Bharata, 2024)
Leadership, organizational culture, and commitment have a very important role in improving the performance of members in the organization. Many organizations, especially government agencies, have problems with leadership, organizational culture, and commitment, thereby influencing employee performance that is less than optimal or poor, as is the case in Lamandau Regency Personnel and Human Resources Development Agency. This research aims to 1) determine the influence of leadership on human employee performance, 2) determine the influence of organizational culture on employee performance, 3) determine the influence of organizational commitment on employee performance and 4) determine the influence of leadership, organizational culture, and organizational commitment to employee performance. The sampling method is a saturated sample so that the entire population is used as a sample. The data analysis used is multiple linear regression analysis. The respondents in this research were 43 employees at the Lamandau Regency Personnel and Human Resources Development Agency. Data collection was carried out by distributing questionnaires via Google Form. The results of the research show that 1) leadership on employee performance in the Personnel and Human Resources Development Agency of Lamandau Regency has a significant influence, 2) organizational culture on employee performance in the Personnel and Resource Development Agency Lamandau Regency people have a significant influence, 3) Organizational commitment to employee performance in the Lamandau Regency Personnel and Human Resources Development Agency has an influence, and 4) Then leadership, organizational culture and organizational commitment have an influence on employee performance in the Personnel Agency and Development of Human Resources in Lamandau Regency due to the results of simultaneous hypothesis testing.